2022
DOI: 10.3389/fnagi.2022.917629
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Polysaccharides in Neurodegenerative Diseases

Abstract: Neurodegenerative diseases (NDs) are characterized by progressive degeneration and necrosis of neurons, including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease and others. There are no existing therapies that correct the progression of these diseases, and current therapies provide merely symptomatic relief. The use of polysaccharides has received significant attention due to extensive biological activities and application prospects. Previous studies suggest that the polysaccharides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 182 publications
0
10
0
Order By: Relevance
“…Dendrobium officinale has been reported to possess several pharmacological properties notably, anticancer [ 3 , 4 ], hepatoprotective [ 4 , 11 , 12 ], anti-inflammatory [ 6 ], antioxidant [ 7 , 38 , 39 ], anti-diabetic [ 2 ], antiangiogenic [ 2 , 3 , 4 , 54 ], immuno-enhancing [ 3 , 10 ], and neuroprotective activities [ 2 , 44 , 55 ]. Many studies have indicated that the bioactive constituents in D. officinale , such as its phenolic acids, flavones and polysaccharides are the main components responsible for the health benefits [ 7 , 21 , 22 , 55 , 56 ]. Remarkably, the polysaccharides found in D. officinale (DOP) have been reported to elicit blood lipid-lowering, sugar-lowering, antioxidant, hepatoprotective, and anti-aging activities [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dendrobium officinale has been reported to possess several pharmacological properties notably, anticancer [ 3 , 4 ], hepatoprotective [ 4 , 11 , 12 ], anti-inflammatory [ 6 ], antioxidant [ 7 , 38 , 39 ], anti-diabetic [ 2 ], antiangiogenic [ 2 , 3 , 4 , 54 ], immuno-enhancing [ 3 , 10 ], and neuroprotective activities [ 2 , 44 , 55 ]. Many studies have indicated that the bioactive constituents in D. officinale , such as its phenolic acids, flavones and polysaccharides are the main components responsible for the health benefits [ 7 , 21 , 22 , 55 , 56 ]. Remarkably, the polysaccharides found in D. officinale (DOP) have been reported to elicit blood lipid-lowering, sugar-lowering, antioxidant, hepatoprotective, and anti-aging activities [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, ncRNAs can play a role in the regulation of nerve cell death, and ncRNAs are expected to become another therapeutic target for AD. It has been found that down-regulation of miR-22 can significantly alleviate the apoptosis of PC-12 cells induced by LPS and achieve the purpose of treating diseases ( Wang Y. et al, 2022 ). Of course, there are many types of nerve cell death, including apoptosis, pyroptosis, necrosis, and ferroptosis ( He et al, 2022 ; Jin et al, 2022 ; Mangalmurti and Lukens, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…AD is the most common ND worldwide with an insidious onset and progressive development [ 4 , 91 ]. It is characterized by progressive impairment of cognition and episodic memory, culminating in the development of dementia [ 92 ].…”
Section: Gut Microbiota Oxidative Stress and Neurodegenerationmentioning
confidence: 99%
“…Progressive neuronal necrosis and degeneration are hallmarks of neurodegenerative diseases (NDs), including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), and multiple sclerosis (MS), which are caused by neurotoxic etiological agents in the brain and surrounding organs. Because of the diverse and complex pathological symptoms, uncertain pathogenesis, restricted clinical examination, difficulty in making an early diagnosis, and lack of treatment options, NDs have imposed significant societal and economic burdens [ 1 , 2 , 3 , 4 ]. The current treatment of NDs mainly focuses on relieving symptoms, and no effective cure is currently available.…”
Section: Introductionmentioning
confidence: 99%